Memristive Circuits for LDPC Decoding - Jussi Poikonen; Eero Lehtonen; Mika Laiho; Jonne Poikonen (Institute of Electrical and Electronics Engineers, 2022)
We present design principles for implementing decoders for low-density parity check codes in CMOL-type memristive circuits. The programmable nonvolatile connectivity enabled by the nanowire arrays in such circuits is used to map the parity check matrix of an LDPC code in the decoder, while decoding operations are realized by a cellular CMOS circuit structure. We perform detailed performance analysis and circuit simulations of example decoders, and estimate how CMOL and memristor characteristics such as the memristor OFF/ON resistance ratio, nanowire resistance, and the total capacitance of the nanowire array affect decoder specification and performance. We also analyze how variation in circuit characteristics and persistent device defects affect the decoders.